A case of welder's pneumoconiosis treated with corticosteroid followed by nintedanib. (2022) - Kaida, Hideyuki; Utsunomiya, Takuhide; Koide, Yohei; Ueda, Yusuke; Wada, Kenji; Yoshida, Yuji; Kinoshita, Yoshiaki; Kushima, Hisako; Ishii, Hiroshi
Abstract: A 32-year-old man who had worked as a welder for 13 years was hospitalized for a fever and hemosputum with dyspnea. He was diagnosed with welding fume-associated lung disease with alveolar hemorrhaging and acute respiratory failure. Despite surviving the acute phase with corticosteroid therapy, hypoxemia persisted after a month and a half, requiring home oxygen therapy. As a result of the introduction of nintedanib, his clinical findings gradually improved, and the patient was weaned from oxygen therapy after six months. Inhalation of a large amount of welding fumes in a short period can cause alveolar hemorrhaging and prolonged pulmonary dysfunction.